Miniature tri‐wideband Sierpinski–Minkowski fractals metamaterial perfect absorber. Issue 7 (15th March 2019) - Amiri, Majid; Tofigh, Farzad; Shariati, Negin; Lipman, Justin; Abolhasan, Mehran
Abstract : With rapidly growing adoption of wireless technologies, requirements for the design of a miniature wideband multi‐resonators are increasing. In this study, a compact fractal‐based metamaterial structure with lumped resistors is described. The structure of the authors proposed absorber is a combination of Sierpinski curve and Minkowski fractal. The new combination provides larger capacitance and inductance in the system enabling perfect absorption at lower frequencies. The final structure with dimensions of 20 × 20 × 1.6 mm 3 and an air gap of 12.5 mm provides three main resonances at frequencies of 2.1, 5.1, and 12.8 GHz with bandwidth (absorption ratio over 90%) of 840 MHz, 1.05 GHz, and 910 MHz, respectively.